2015
DOI: 10.1111/eff.12240
|View full text |Cite
|
Sign up to set email alerts
|

Movement of three stream‐resident balitoroid loaches and a goby in a Hong Kong hillstream

Abstract: We undertook a mark–recapture study of three pool‐dwelling balitoroid loaches and a nonmigratory goby in a Hong Kong hillstream, which extended over a 35‐week period. The target species were Pseudogastromyzon myersi and Liniparhomaloptera disparis (Balitoridae), Schistura fasciolata (Nemacheilidae) and Rhinogobius duospilus (Gobiidae). Recapture rates of tagged individuals were high (58% overall), especially for the abundant R. duospilus (70% of 412 tagged) and P. myersi (57% of 762 tagged). At the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Control pools were subject to temporary removal of stones, wading and electrofishing, but no macroconsumers were removed. No block nets were installed because mark–recapture studies in Hong Kong streams have demonstrated the highly sedentary nature of Hong Kong fishes and the shrimp M. hainanense (Mantel & Dudgeon, ; Ho & Dudgeon, ), suggesting that recolonisation of defaunated pools during the 4‐week study period would have been negligible (see also Martin‐Smith et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Control pools were subject to temporary removal of stones, wading and electrofishing, but no macroconsumers were removed. No block nets were installed because mark–recapture studies in Hong Kong streams have demonstrated the highly sedentary nature of Hong Kong fishes and the shrimp M. hainanense (Mantel & Dudgeon, ; Ho & Dudgeon, ), suggesting that recolonisation of defaunated pools during the 4‐week study period would have been negligible (see also Martin‐Smith et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…S. fasciolata and P. myersi are well adapted to fast-flowing streams, but they may be swept downstream during a downpour in the rainy season. A recent markrecapture study in Hong Kong reveals a marked difference in their mobility: rheophilic behaviour is common in balitoroid loaches, and P. myersi shows a particularly strong tendency to move upstream (Ho and Dudgeon, 2015). In contrast, S. fasciola is sedentary with limited movement along the stream.…”
Section: Phylogeographic Inferencementioning
confidence: 99%
“…Indeed, recent population genetic studies of freshwater shrimp, Caridina cantonensis, revealed strong genetic divergence and a low level of gene flow among populations within and among drainage systems (Tsang et al, 2016). The freshwater goby, Rhinogobius duospilus, which is a sedentary stream fish (Ho and Dudgeon, 2015), showed even stronger population differentiation and the pattern of population structure follows the Late Pleistocene paleodrainage pattern (Wu et al, 2016). However, with only two ecologically different and phylogenetically distant freshwater species examined in this region, it is unclear whether the observed patterns are common in multiple freshwater taxa in Hong Kong, and whether there were general historical causes that similarly shaped the population genetic structure of local stream inhabitants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations